Policing Across Organisational Boundaries Developments in Theory and Practice - Dupont, Benoît; Whelan, Chad; Manning, Peter K. (Taylor & Francis, 2019)
This book promotes new theoretical frameworks and research questions that seek to advance knowledge of policing across internal and external organisational boundaries, specifically at the structural level of analysis. It addresses police theory, policy and practice, and also provides new directions for future research on intra- and inter-organisational policing. Analysing boundaries is of increasing global importance for policing policy and practice. Boundaries reflect the division-of-labour inherent to complex organisations and their specialist units. In order to operate effectively, however, these boundaries must be crossed, and strong and reliable linkages must be built. Intra-organisationally, it is vital to understand how specialist units form and function and interact with other units. Inter-organisationally, it is fundamental to recognise the place of boundaries in contexts such as international police cooperation. This book was originally published as a special issue of Policing and Society. Chapters 3 and 4 are available Open Access at https://www.routledge.com/products/9780367182915.